PENERAPAN METODE DEMONSTRASI PADA PEMBELAJARAN IPA DALAM MENINGKATKAN MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA DI KELAS V SD NEGERI 28 KELAKIK - Pujiastuti, Ami; Nugraha, Asep Eka; Apsari, Nurul (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2023)
This classroom action research aims to increase learning motivation and student learning outcomes by applying the demonstration method in science learning. In particular, the researcher chose the demonstration method because in the learning process he used demonstrations or direct practice to clarify the meaning, process, and workings of an object related to science learning material in class V SD Negeri 28 Kelakik. The research method used is classroom action research (CAR) which refers to Arikunto's model, and the approach in this study uses an empirical approach that describes and explains the actual situation. Data collection techniques in this study used tests and non-tests. The results of the study at the pre-action stage average learning planning (APKG I) was 66.16%, the average learning implementation (APKG II) was 66.76%, the average learning motivation was 58.08%, and the average test results of learning by 66.66%. Whereas in the first cycle the average lesson plan (APKG I) was 76.16%, the average learning implementation (APKG II) was 76.18%, the average learning motivation was 72.41%, and the average test results of learning by 85.00%. In cycle II the average learning planning (APKG I) was 89.08%, the average learning implementation assessment (APKG II) was 94.16%, the average learning motivation assessment was 84.25%, and the average the average of the learning outcomes test is 99.16%. So that the range of improvement for each cycle from APKG I was 77.13%, APKG II was 79.19% which was categorized as good, student learning motivation was 71.58% and categorized as motivated, and the range of improvement on student learning achievement tests was 84.09 %. Thus it can be proven that the application of the demonstration method is very effective in increasing learning motivation and student learning outcomes